Implementasi Metode Iqra’ Dan Metode Tilawati Dalam Pembelajaran Al-Qur’an Di Madrasah Diniyah Al-falah Modung Bangkalan - Subhan Adi Santoso; Maftuhah; Suharsono (STIT Muhammadiyah Paciran Lamongan, 2018)
Abstract: The role of the Qur'an in guiding and directing human life, then learning to read, understand and live the Qur'an to be practiced in everyday life is a duty for every Muslim. But unfortunately, the current phenomenon is not so. There are still many good Muslims from among children, adolescents, adults, even parents can not read and write the letter of the Qur'an (illiteracy of the Qur'an). Such a situation raises concerns especially for Muslims in Indonesia. The author will choose the location of research at Madrasah Diniyah Al-falah Modung Bangkalan. The subject of the research is the headmaster Waka curriculum, Ustadz / dzh, and students. In this study the authors use three kinds of data collection techniques that is the method of observation or observation, interview method, documentation method. 1 Implementation of Iqra 'and Tilawati methods in Madrasah Diniyah Al-Falah Modung Bangkalan such as: the use of CBSA system (How to Study Active Students); the use of direct reading and Individual reading techniques (reading individually in front of ustadz / ustadzah). 2 The implementation equation between Iqra 'and Tilawati methods are: the use of CBSA system (Active Learning Student), the use of Direct Spelling technique in its reading, the use of Individual technique (individual reading in front of ustadz / ustadzah), and compiled / Variative. As for the difference in the implementation of Iqra 'and Tilawati methods are: for the Tilawati method using the National Standard Rost song, while for Iqra' method it is not allowed to use the song even though Irott Murottal; in Iqra 'method using sound approach for difficult letters in its pronunciation, whereas in Tilawati method it is emphasized to pronounce letters according to the right makhraj; besides using Individual reading technique on Tilawati method also using classical technique, whereas in Iqra 'method only use Individual technique only. 3 Factors that support the implementation of Iqra 'and Tilawati methods in Madrasah Diniyah Al-Falah Modung Bangkalan, namely: the availability of props and tapes Murottal (with some type of rhythm of the song); to shorten the time, as long as Individual ustadz / ustadzah assisted by an assistant so that the reading achievement of students can be monitored maximally and santri have a lot of maximal learning time as well.